A LaCl3-based lithium superionic conductor compatible with lithium metal - Yichen Yin; Jingtian Yang; Jinda Luo; Gongxun Lu; Zhongyuan Huang; Jianping Wang; Pai Li; Feng Li; Yechao Wu; Te Tian; Yufeng Meng; Hongsheng Mo; et al. (Nature, 2023)
Inorganic superionic conductors possess high ionic conductivity and excellent thermal stability but their poor interfacial compatibility with lithium metal electrodes precludes application in all-solid-state lithium metal batteries. Here we report a LaCl3-based lithium superionic conductor possessing excellent interfacial compatibility with lithium metal electrodes. In contrast to a Li3MCl6 (M = Y, In, Sc and Ho) electrolyte lattice, the UCl3-type LaCl3 lattice has large, one-dimensional channels for rapid Li+ conduction, interconnected by La vacancies via Ta doping and resulting in a three-dimensional Li+ migration network. The optimized Li0.388Ta0.238La0.475Cl3 electrolyte exhibits Li+ conductivity of 3.02 mS cm−1 at 30 °C and a low activation energy of 0.197 eV. It also generates a gradient interfacial passivation layer to stabilize the Li metal electrode for long-term cycling of a Li–Li symmetric cell (1 mAh cm−2) for more than 5,000 h. When directly coupled with an uncoated LiNi0.5Co0.2Mn0.3O2 cathode and bare Li metal anode, the Li0.388Ta0.238La0.475Cl3 electrolyte enables a solid battery to run for more than 100 cycles with a cutoff voltage of 4.35 V and areal capacity of more than 1 mAh cm−2. We also demonstrate rapid Li+ conduction in lanthanide metal chlorides (LnCl3; Ln = La, Ce, Nd, Sm and Gd), suggesting that the LnCl3 solid electrolyte system could provide further developments in conductivity and utility.